Iron Oxide Nanoparticles as Imaging and Therapeutic Agents for Atherosclerosis - Talev, Joshua; Kanwar, Jagat Rakesh (Seminars in Thrombosis and Hemostasis, 2020)
Atherosclerosis is the major cause of cardiovascular diseases and is the leading cause of mortality worldwide. Iron oxide nanoparticles have emerged as potential diagnostic and therapeutic agents for a wide range of conditions. To date, the theranostic applications of iron oxide nanoparticles have been studied mainly in cancer, but atherosclerosis has not received the same attention. Therefore, it appears appropriate to review the current and future applications of iron oxide nanoparticles for the diagnosis and therapy of atherosclerosis. This review will first discuss current imaging techniques for the diagnosis of atherosclerosis as well as their limitations. It will then discuss the role of nanotechnology for molecular imaging of atherosclerosis and the benefits of this approach as well as reviewing current developments in the field including single, bi-, and tri-modal imaging. Next, it will discuss the role of nanotechnology for therapies of atherosclerosis with a focus on nanotheranostics, concluding with a look at the challenges faced by nanoparticle-based imaging and therapy of atherosclerosis as well as a look at future prospects.
Keywords: iron oxide; nanoparticle; atherosclerosis; diagnosis; therapy